How can competencies in minor surgery in general practice be increased?: assessing the effect of a compact intervention in postgraduate training : a mixed-methodsstudy - Schwill, Simon; Krug, Katja; Poppleton, Aaron; Reith, Dorothee; Senft, Jonas; Szecsenyi, Joachim; Stengel, Sandra (BMJ open, 2022)
Objectives We aimed to assess general practice (GP) trainees’ self-perception of surgical competencies and to explore longitudinal effects of a compact intervention. - Design We performed a mixed-methods study including a before and after comparison in the intervention group (IG), a comparison of attendees and non-attendees (control group (CG)) and a qualitative evaluation of the intervention. Competencies were self-assessed through surveys. Semi-structured interviews were performed after 9 months. - Setting In 2019, a 2-day voluntary seminar focussing on minor surgery/injuries was offered on 13 occasions by educators from KWBW Verbundweiterbildungplus (Competence Centre for Postgraduate Medical Education Baden-Württemberg). - Participants All enrolled GP trainees were offered participation. GP trainees who did not attend a seminar (non-attendees) were recruited for CG after the 13th intervention. - Intervention Attendees took part in an interactive, GP-oriented short course incorporating 270 min of focused minor surgery/injuries training (compact intervention) on the second day of the 2-day seminar. - Results 326 GP trainees (IG: n=257; CG: n=69) participated in the study. 17 attendees were interviewed. CG had more often experienced a surgical rotation (p=0.03) and reported higher interest in performing minor surgery in future practice (p=0.03). GP trainees self-rated their all-round competency in minor surgery as average (IG: 3.0±1.0, CG: 3.2±0.9, IG:CG p=0.06). After the intervention, attendees felt that surgical skills should be a core component of GP vocational training (p=0.05). After 9 months, attendees remembered a variety of content and valued the interactive, case-oriented, peer-to-peer approach in a mixed learning group. Some attendees reported they had started to overcome competency gaps in minor surgery. - Conclusions A compact intervention in minor surgery provides an ‘intense’ stimulus which could foster positive attitudes towards minor surgery and promote longitudinal personal development of related competencies in GP trainees, including those with little interest in surgery. Such measures appear crucial to support individual progress of GP trainees to provide comprehensive primary care.
Gesehen am 27.01.2023